The Anxiety Level of Cancer Patients Undergoing Radiotherapy at Universitas Andalas Hospital - Trisno, Assyifa Azzahra Dwi; Hanum, Fathiya Juwita; Hendriati, Hendriati; Silvia, Nelmi; Pertiwi, Dian; Sy, Elmatris (http://dharmais.co.id/, 2025)
Background: Radiotherapy is one of the most commonly used treatments for cancer. Radiotherapy works by using high-energy particles or waves, such as X-rays, gamma rays, electron beams, or protons, to destroy or damage cancer cells. Anxiety is an emotional response that arises when a person experiences stress. Patients diagnosed with cancer will experience anxiety, and the anxiety increases in patients undergoing radiotherapy. Anxiety in radiotherapy generally occurs due to a lack of information, side effects of treatment, and radiation procedures. This study aims to determine the description of the anxiety level of cancer patients undergoing radiotherapy at Universitas Andalas Hospital.Method: This study is a quantitative descriptive study with a cross-sectional approach that examines the description of the anxiety level of cancer patients undergoing radiotherapy at Universitas Andalas Hospital. Anxiety levels were measured using the State Trait Anxiety Inventory (STAI) questionnaire.Results: The sample in this study was 62 cancer patients undergoing radiotherapy. The results of the study were obtained in the A-State section, 64.5% experienced mild anxiety, 27.4% experienced moderate anxiety, and 8.1% experienced severe anxiety. The results of the A-Trait section 53.2% experienced mild anxiety, 43.6% experienced moderate anxiety, and 3.2% experienced severe anxiety. The trait section of anxiety tends to be more severe than the state section.Conclusion: The anxiety level of cancer patients undergoing radiotherapy at Andalas University Hospital, A-State, and A-Trait is mostly at a mild level. The results of the study can be used as a source of information to consider a psychological approach to patient treatment. However, further researchers can analyze the relationship between variables that influence the level of anxiety